A study of the glazing techniques and provenances of Tang sancai glazes using elemental and lead isotope analyses - Shen, J.Y.; Henderson, J.; Evans, J.; Chenery, S.; Zhao, F.Y. (Wiley, 2018)
This study discusses the elemental compositions and lead isotope ratios of Tang sancai glazes unearthed from the Huangpu kiln, Huangye kiln and two Tang sancai tomb sites. The various glazes feature distinct lead isotope ratios and trace element characteristics, which can be interpreted as evidence for the use of different lead ore deposits and siliceous raw materials in the glazes. This is a strong indication that lead isotopes combined with trace element analysis could be used as a viable approach for identifying the provenance of Tang sancai of unknown origin by linking them to kiln sites, This provenance technique could be significant in the interpretation of ancient ceramic trade and communication patterns. In this study, the provenance of several Tang sancai glazes of uncertain origin were determined using this method: some Tang sancai wares unearthed in Xi'an City were produced in the kiln near Luoyang City and then traded to Xi'an City, providing an idea of ancient Tang sancai ceramic trade routes